Innovating for diversity : lessons from top companies achieving business success through inclusivity - Ceccarelli, Bertina; Tedrick, Susanne (John Wiley & Sons, 2023)
Discover what business visionaries on the frontiers of diverse and equitable hiring are doing to drive change in their organizations In Innovating for Diversity: Lessons from Top Companies That are Disrupting Old Practices to Achieve Inclusivity, Equity and Business Success, renowned Diversity, Equity, and Inclusion (DEI) and tech specialists Bertina Ceccarelli and Susanne Tedrick reframe the DEI discussion and move it beyond a human resources issue. While it's well established that diverse teams help to advance innovation, the authors explain how principles of innovation can be applied to building highly effective and sustainable diversity, equity and inclusion (DEI) practices embraced by executives across an organization. You'll be inspired by leaders at top companies who identified root causes of limited DEI progress and created smart, bold solutions for increasing representation, developing future talent, and advancing the careers of people often overlooked. In the book, you'll also find: Introductions to the people and companies who have innovated their approaches to diverse hiring, retention, and advancement, and enjoyed pronounced impact on their bottom lines Profiles of committed leaders driving the change towards a more diverse and inclusive workforce Strategies for breaking down the cultural and organizational barriers in companies that remain in place and prevent transformative change A critical resource for senior-level business professionals, managers, and executives, Innovating for Diversity will also prove to be invaluable for people seeking to build their careers from the ground up.